Crystal structure of bis{2-(tert-butyl)-6-((E)-((4-((E)-1-(methoxyimino)ethyl)phenyl)imino)methyl)phenolato-κ2N,O}zinc(II), C40H46N4O4Zn - Zhao Ji-Xing; Wu Lei-Fang; Chen Da-Qun (Zeitschrift für Kristallographie - New Crystal Structures)
C40H46N4O4Zn, monoclinic, P21/n (no. 14), a = 12.0198(4) Å, b = 28.0212(9) Å, c = 12.0655(4) Å, β = 110.727(2)°, V = 3800.8(2) Å3, Z = 4, Rgt(F) = 0.0442, wRref(F2) = 0.1076, T = 173(2) K.